Pelatihan Talempong Kreasi Di Sanggar Saandiko Bukittinggi - Demillah Diti Salsabil; Harisnal Hadi (FBS Universitas Negeri Padang, 2022)
This study aims to determine and describe how the creation of talempong training at Sanggar Saandiko Bukittinggi. The type of research conducted is qualitative research, with the object of research being members of Sanggar Saandiko Bukittinggi. The data collected in this study were in the form of written data, interviews, and observations. The results showed that the target of talempong creation training was at Sanggar Saandiko, so it can be concluded that in the training process the trainers managed to provide good training using the lecture method, demonstration method, and practice method/ drill. To achieve the goal of producing and developing creative talent, of course, to be even better, the trainer continues to provide a training process for studio members so that the abilities obtained continue to increase.